2020
DOI: 10.1186/s12885-020-07036-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of type 2 diabetes mellitus and antidiabetic medication with risk of prostate cancer: a population-based case-control study

Abstract: Background: Prostate cancer (PCa) and type 2 diabetes mellitus (T2DM) are prevalent conditions that often occur concomitantly. However, many aspects of the impact of T2DM, particularly the duration of T2DM and antidiabetic medications, on PCa risk are poorly understood. Methods: To assess the association of duration of T2DM and antidiabetic medication with PCa risk, we designed a matched case-control study, including 31,415 men with PCa and 154,812 PCa-free men in Prostate Cancer data Base Sweden (PCBaSe) 4.1.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…In humans, there is an inverse association between diabetes mellitus (or metabolic syndrome) and PCa [ 118 119 ], which has been shown in studies conducted mainly in the white people [ 120 121 122 ]. However, in Taiwan we demonstrated that diabetes patients have a significantly higher incidence of [ 123 ] and mortality from [ 124 ] PCa.…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…In humans, there is an inverse association between diabetes mellitus (or metabolic syndrome) and PCa [ 118 119 ], which has been shown in studies conducted mainly in the white people [ 120 121 122 ]. However, in Taiwan we demonstrated that diabetes patients have a significantly higher incidence of [ 123 ] and mortality from [ 124 ] PCa.…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…So, its forceful activation to express can be a potential therapeutic approach[ 43 ]. Therefore, both metformin and certain therapies help in blocking cell cycle progression by reducing mTOR activity[ 44 ]. Hypogonadism (decrease in level of testosterone) is also found associated with both diabetes and prostate cancer (PCa).…”
Section: Prostate Cancer and Diabetes Linco1128mentioning
confidence: 99%
“…The scope of such studies is extremely broad owing to the range of datasets currently included. To date, most studies have investigated risks associated with other comorbid diseases (e.g., diabetes [ 27 ]) or specific medications (e.g., 5-apha reductase inhibitors for benign hyperplasia [ 28 ], testosterone replacement therapy [ 29 ], anti-inflammatory medications [ 30 ], antidiabetic medications [ 31 ] and the antihypertensive drug spironolactone, known to have antiandrogenic effects [ 32 ]). In addition, case–control studies using PCBaSe have also examined immigrant status [ 33 ], fatherhood status [ 34 , 35 ] and family history of PCa [ 36 ].…”
Section: The Value Of Rwd In Understanding Pca—examples From Swedimentioning
confidence: 99%